Forest statistics for North-Central Alabama, 2000 - Brown, Mark J.; Sheffield, Raymond M. (USDA Forest Service, Southern Research Station, 2001)
This report summarizes a 2000 inventory of the forest resources of a 15-county area of Alabama. Major findings are highlighted in text and graphics; detailed data are presented in 49 tables.
Keywords: Statistik; Forest surveys -- Alabama; Forests and forestry -- Alabama -- Statistics; Timber -- Alabama -- Statistics; Waldbestand; Holzmassenermittlung; Alabama -- Nord; Datensammlung